2017
DOI: 10.1371/journal.pone.0190260
|View full text |Cite
|
Sign up to set email alerts
|

Higher retention and viral suppression with adolescent-focused HIV clinic in South Africa

Abstract: ObjectiveTo determine retention in care and virologic suppression among HIV-infected adolescents and young adults attending an adolescent-friendly clinic compared to those attending the standard pediatric clinic at the same site.DesignRetrospective cohort analysis.SettingGovernment supported, hospital-based antiretroviral clinic in KwaZulu-Natal, South Africa.ParticipantsTwo hundred forty-one perinatally HIV-infected adolescents and young adults aged 13 to 24 years attending an adolescent-friendly clinic or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 42 publications
8
100
1
Order By: Relevance
“…A recent study conducted in Canada reported that a quarter of transitioned patients were no longer engaged in care [55]. Although these data are from high-income settings, we may expect similar findings in low-resource settings where report of transition outcomes are less common [48,50]. Descriptions of ongoing research efforts to capture transition outcomes in African settings and how they differ from high- and middle-income settings are necessary in order to identify key steps in the HIV cascade for interventions.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…A recent study conducted in Canada reported that a quarter of transitioned patients were no longer engaged in care [55]. Although these data are from high-income settings, we may expect similar findings in low-resource settings where report of transition outcomes are less common [48,50]. Descriptions of ongoing research efforts to capture transition outcomes in African settings and how they differ from high- and middle-income settings are necessary in order to identify key steps in the HIV cascade for interventions.…”
Section: Discussionmentioning
confidence: 66%
“…Support groups and greater involvement of adolescent healthcare providers have been suggested by healthcare providers themselves to facilitate transition [22,30]. Teen clinics have also been found in a small number of studies to improve retention compared to the standard model of care which is the most prevalent [48,50]. Although these youth-focused health services may improve their retention in HIV care, it is difficult to generalize study results due to their limited numbers, sample sizes, and short follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work in CCASA has demonstrated the importance of ensuring a comprehensive approach to adolescent HIV care in which factors affecting treatment outcomes can be identified and addressed before the transitioning process begins [73,78,79]. Peer support may improve outcomes [55,98]; however, young people across CCASA, EE and AP who are part of stigmatized or criminalized groups including MSM, sex workers, PWID or their sexual partners may face particular challenges in accessing this. Many adolescent clinics in CCASA are admitting MSM youth who subsequently identify as transgender females.…”
Section: Resultsmentioning
confidence: 99%